Alterations in dendrite and spine morphology of cortical pyramidal neurons in DISC1-binding zinc finger protein (DBZ) knockout mice - Koyama, Yoshihisa; Hattori, Tsuyoshi; Nishida, Tomoki; Hori, Osamu; Tohyama, Masaya (Frontiers in Neuroanatomy, 2015)
Dendrite and dendritic spine formation are crucial for proper brain function. DISC1-binding zinc finger protein (DBZ) was first identified as a Disrupted-In-Schizophrenia1 (DISC1) binding partner. DBZ is highly expressed in the cerebral cortex of developing and adult rodents and is involved in neurite formation, cell positioning, and the development of interneurons and oligodendrocytes. The functional roles of DBZ in postnatal brain remain unknown; thus we investigated cortical pyramidal neuron morphology in DBZ knockout (KO) mice. Morphological analyses by Golgi staining alone in DBZ KO mice revealed decreased dendritic arborization, increased spine density. A morphological analysis of the spines revealed markedly increased numbers of thin spines. To investigate whole spine structure in detail, electron tomographic analysis using ultra-high voltage electron microscopy (UHVEM) combined with Golgi staining was performed. Tomograms and three-dimensional models of spines revealed that the spines of DBZ KO mice exhibited two types of characteristic morphology, filopodia-like spines and abnormal thin-necked spines having an extremely thin spine neck. Moreover, conventional electron microscopy revealed significantly decreased number of postsynaptic densities (PSDs) in spines of DBZ KO mice. In conclusion, DBZ deficiency impairs the morphogenesis of dendrites and spines in cortical pyramidal neurons.